A GHz Operating CMOS Compatible ScAlN Based SAW Resonator Used for Surface Acoustic Waves/Spin Waves Coupling - Zdru, I.; Nastase, Claudia; Hess, L. N.; Ciubotaru, F.; Nicoloiu, Alexandra; Vasilache, Dan; Dekkers, M.; Geilen, Moritz; Ciornei, C.; Boldeiu, George; Dinescu, A.; Adelmann, C.; et al. (IEEE Electron Device Letters, 2022)
ScAlN/Si, a CMOS compatible material, was used to manufacture GHz operating surface acoustic wave devices, targeting manipulation and control of spin waves via SAW devices. A thin ScAlN piezoelectric layer was deposited on high resistivity (111) oriented Silicon and two port SAW devices were processed using advanced nanolithographic techniques. The Surface Acoustic Wave and Spin Wave coupling was performed via a thin magnetostrictive layer (Ni) placed between the SAWs interdigitated transducers. Both Rayleigh (4.67 GHz) and Sezawa (8.05 GHz) propagation modes could be observed. The amplitude of the S21 parameter around the two resonances was measured for values of the magnetic field μ0H from-280 to +280 mT, at different angles ( θ ) between the SAW propagation direction and the magnetic field direction. A maximum decrease of 2.54 dB occurred in S21 for the Rayleigh mode at μ0H =-90 mT, and of 7.24 dB for the Sezawa mode at μ0H =-203 mT, both at θ = 45°. These values were extracted from time gated processing of the frequency domain raw data. Nonreciprocity associated to the coupling was analyzed for the two propagation modes.
CRIS-Team Scopus Importer:2023-03-27
Keywords: Magnetic field; Rayleigh mode; Sc doped AlN; Sezawa mode; Spin waves; Surface acoustic waves